Population structure and genetic diversity in Gynaikothrips uzeli (Thysanoptera: Phlaeothripidae): Is there a correlation between genetic and geographic proximity? - Mascarenhas, André Luiz S; Waldschmidt, Ana Maria; Silva, Juvenal Cordeiro (Genetics and Molecular Research, 2015)
Gynaikothrips uzeli (Thysanoptera: Phlaeothripidae) is a minuscule insect species, which forms galls, is subsocial, and parthenogenetic. It is associated with Ficus benjamina L. (Moraceae) and has a pantropical occurrence. The paucity of genetic studies on the order Thysanoptera led us to use inter-simple sequence repeat molecular marker to assess intra- and inter-gall, as well as intra- and inter-site, genetic variability and population structure of G. uzeli. Analyses indicated low genetic variability, probably related to haplodiploidy, genetic drift, the galling habit, and the low dispersal ability of G. uzeli. Populations were highly structured, with higher variation within populations than among them. Geographic distance does not appear to affect structure and genetic diversity, the latter being influenced by G. uzeli’s bioecological traits, by numerous introductions during a short period, and by a possible recent, common ancestry. © FUNPEC-RP.
Keywords: Genomic Dna; Microsatellite Dna; Adult; Behavior, Animals; Biological Trait; Controlled Study; Galling Habit; Gene Sequence; Genetic Association; Genetic Correlation; Genetic Distance; Genetic Drift; Genetic Marker; Polymorphism, Genetic; Genetic Variability; Geographic Distribution; Gynaikothrips Uzeli; Haploidy; Heterozygosity; Human; Inter Simple Sequence Repeat; Population Genetic Structure; Thysanoptera; Allele; Animals; Classification; Cluster Analysis; Genetic Variation; Genetics; Evolution, Molecular; Phylogeny; Genetics, Population; Thysanoptera; Ficus Benjamina; Gynaikothrips; Hexapoda; Moraceae; Phlaeothripidae; Thysanoptera; Alleles; Animal; Cluster Analysis; Evolution, Molecular; Genetic Variation; Genetics, Population; Microsatellite Repeats; Phylogeny; Thysanoptera